66.4: Large‐Sized Flexible Lighting with Highly Efficient OLEDs. Issue 1 (1st July 2013) - Ohsawa, Nobuharu; Idojiri, Satoru; Kumakura, Kayo; Obana, Saki; Kobayashi, Yuka; Kataniwa, Masatoshi; Ohide, Takayuki; Ohno, Masakatsu; Adachi, Hiroki; Sakamoto, Naoya; Yatsuzuka, Shota; Aoyama, Tomoya; et al.
Abstract: A flexible OLED lighting demonstrating over 130 lm/W by combining a highly efficient OLED and a light outcoupling film has been developed. Furthermore, a prototype 360 × 300‐mm flexible OLED lighting was successfully fabricated by using transfer technology.